Chromosome analysis results of first-second trimester anomaly screening tests: Single center experience - Boso, Banu; Soysal, Cenk; Sucu, Mete; Cansun Demir, Suleyman (Annals of Medical Research, 2021)
Aim: The Objective of our study was to evaluate the chromosomal analysis results that were obtained from amniocentesis, cordocentesis and chorionic villus sampling (CVS) inpatients whom had applied to the perinatology unit of Cukurova University Faculty of Medicine gynecology and obstetrics clinic with high risk in terms of chromosome anomaly according to Ultrasonography (USG).Material and Methods: Our study was conducted as a retrospective pattern. CVS, amniocentesis and cordosentesis were performed in 1298 pregnant women whom had applied to the Çukurova University Faculty of Medicine, Gynecology and Obstetrics Clinic, Perinatology Unit in the date interval between 1st December 2014-31st December 2016 with the indication of abnormal maternal serum screening tests, maternal request because of advanced maternal age, history of fetal anomaly with previous pregnancies, history of relatives with Trisomy 21, fetal abnormalities or signs of trisomy which were detected by ultrasonography and only depending on maternal request without any risk factors. Data obtained in the study were assessed using the SPSS (Statistical Package for Social Sciences) 22.0 package program. The relationships between categorical variables were determined by Chi-Square test. Relationship between normal distribution-matched, numerical data were assessed by ANOVA, Independent Sample t-test, and relationship between non-normal distributions of numerical data were assessed using Mann-Whitney U and Wilcoxon Test. Statistical significance level was determined as p 0.05.Results: Fetal anomalies were observed in 28.9% (n: 366) of the patients while 369 (28.4%) of the 1298 patients who had prenatal diagnosis had abnormalities in the maternal screening results. No chromosomal abnormalities were detected in 1120 (86.2%) of the 1298 patients who were taken into the study. 49 patients had Trisomy 21, 27 patients had Trisomy18 and 14 patients had Trisomy13. Turner syndrome was seen in 10 of thepatients. In our study, chromosomal abnormality rate of patients with more than one minor marker was found to be statistically significant (p: 0.01). Chromosomal anomaly was detected in 319 (8.4%) of 349 patients with combined test. Chromosomal anomaly was detected in 70 (19.1%) of the 366 patients who detected fetal anomaly. Chromosomal anomaly was detected in 27 (24.1%) of the 112 increased NT patients.Conclusion: In our study, 1298 invasive procedures are listed as follows; amniocentesis was performed in 841 (64.8%), cordocentesis in 57 patients (4.4%) and CVS in 400 patients (30.8%). As a result of karyotype analysis of the patients, nochromosomal anomaly was detected in 1120 patients (86.28%). In 178 patients, chromosomal anomaly (13.71%) was detected. This study aimed to determine the prevalence of fetal chromosomal anomaly in the Mediterranean region by determining the prevalence of invasive prenatal test indications and evaluating the results of invasive prenatal tests performed in our clinic in the 2-year period.